Comparing boy and girl arsonists: crisis, family, and crime scene characteristics - Roe-Sepowitz, Dominique E. (Legal and criminological psychology, 2011)
Objective. Juvenile arson offenders have received increasing attention due to the high human and financial cost of arson in the USA. This study examines the similarities and differences between male and female juvenile arson offenders regarding family crisis, school issues, mental health, family characteristics, crime descriptions, and past delinquency. Method. The sample consists of 217 male and 114 female juveniles charged with an arson-related charge from a large southern state over a 5-year period from 2000 to 2005. Results. Female juvenile arsonists more often reported a significant crisis within their family in the past year when compared to male juvenile arsonists. Most of the juvenile arson offenders attended school regularly but girls had greater issues with tardiness or truancy than boys. Girl arsonists more often reported a history of childhood abuse, higher scores on a suicide ideation scale and were more likely to set fire at school. Boy arsonists were more likely to have greater mental health problems, report gang involvement, a history of prior delinquency and prior arson, and were found to set fires at their residence when compared to girl arsonists. Instrumental versus expressive reasons for the arson behaviour are discussed. Conclusion. These findings suggest strongly that boy and girls arson offenders are dissimilar enough to require unique assessment and treatment.